Nanopore Sequencing in Blood Diseases: A Wide Range of Opportunities - Minervini, Crescenzio Francesco; Cumbo, Cosimo; Orsini, Paola; Anelli, Luisa; Zagaria, Antonella; Specchia, Giorgina; Albano, Francesco (Frontiers in Genetics, 2020)
The molecular pathogenesis of hematological diseases is often driven by genetic and epigenetic alterations. Next-generation sequencing has considerably increased our genomic knowledge of these disorders becoming ever more widespread in clinical practice. In 2012 Oxford Nanopore Technologies (ONT) released the MinION, the first long-read nanopore-based sequencer, overcoming the main limits of short-reads sequences generation. In the last years, several nanopore sequencing approaches have been performed in various “-omic” sciences; this review focuses on the challenge to introduce ONT devices in the hematological field, showing advantages, disadvantages and future perspectives of this technology in the precision medicine era.